PERLINDUNGAN HUKUM BAGI TENAGA KERJA WAKTU TERTENTU DI KABUPATEN INDRAGIRI HILIR - Syariffudin; Nurhan (Fakultas Hukum Universitas Islam Indragiri, 2023)
The basis of labor law in Indonesia is regulated in Article 27 paragraph (2) of the 1945 Constitution which states that